Zooxanthellar symbiosis in planula larvae of the coral Pocillopora damicornis - Gaither, Michelle R. (2010)
We characterized the planular-zooxanthellae symbiosis of the coral Pocillopora damicornis using criteria that are familiar in studies on corals. Similar to adult corals, planulae exhibited photoacclimation, as changes in symbiont chlorophyll a (chl a); changes in the light-saturation constant for photosynthesis (I(k)); and, at insufficient light, fewer zooxanthellae, decreased respiration, increased weight loss, and increased sensitivity to photoinhibition. Numbers of zooxanthellae in newly-released planulae varied by at least three-fold within broods. Planulae with low versus high numbers of zooxanthellae (termed pale versus dark planulae, respectively) did not differ in symbiont chl-a content, I(k), or biomass-specific rate of dark respiration. Pale planulae had lower rates of photosynthesis, but this difference vanished after three weeks, when zooxanthellar numbers increased by 225% in pale planulae and by 31% in dark planulae. Numbers of zooxanthellae also increased significantly in planulae cultured in ammonium-enriched seawater; ammonium also apparently prevented weight loss and induced settlement. Approximately 70% of photosynthetically-fixed carbon (labeled using (14)C) apparently was translocated from the zooxanthellae to their host. A comparison of planulae cultured at 0.3% versus 11% sunlight suggested that photosynthesis provided ~ 31% of the energy utilized by the latter. Overall, we conclude that the physiology of symbiosis in planulae of P. damicornis is broadly similar to symbiosis physiology in adult corals.